2012
DOI: 10.5402/2012/748080
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perceptions of Environmental Hazards and Human Reproduction: A Community-Based Survey

Abstract: Objectives. We have investigated the Australian public's perceived risks on human reproductive health from a number of identified environmental hazards. Methods. A sample of 1261 subjects was interviewed. This interview included specific questions related to perceived risks of certain environmental hazards to human reproductive health. Results. Women were almost twice as likely to rank all hazards as harmful or very harmful to human reproduction than men. Age also influenced perceived risk with those in the 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
(22 reference statements)
1
14
0
Order By: Relevance
“…EU-wide surveys (7,8) indicate that people across Europe are still concerned about the potential adverse health impact of RF EMF exposure from cell phones and base stations. Similar concerns are reported from Australia, (9) Taiwan, (10) and New Zealand. (11) In other parts of the world, for example, the United States, RF EMF is debated too, but is not a core concern.…”
Section: The Emf Issuesupporting
confidence: 81%
“…EU-wide surveys (7,8) indicate that people across Europe are still concerned about the potential adverse health impact of RF EMF exposure from cell phones and base stations. Similar concerns are reported from Australia, (9) Taiwan, (10) and New Zealand. (11) In other parts of the world, for example, the United States, RF EMF is debated too, but is not a core concern.…”
Section: The Emf Issuesupporting
confidence: 81%
“…Generally, age is an important factor for vulnerability to heat waves since those who are older are known to be at risk during a heat wave [52]. A study conducted to examine the Australian public’s perceived risks on a number of environmental hazards found that older participants had a high risk perception [30]. Nonetheless, contrasting findings between age and risk perception to environmental hazards has been reported in another study [53].…”
Section: Discussionmentioning
confidence: 99%
“…For example, age has been found to be positively correlated with risk perception to hazards [28], although negative correlations have also been reported [29]. Gender is often found to be an important determinant of risk perception as women perceive risks more than men [30]. In addition, individuals with a high income and education level have been found to have a lower perception of risks [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Risk perceptions associated with environmental hazards have largely explored technologies, reproductive health, and socioeconomic and racial differences in hazard exposures [21][22][23][24][25][26][27][28][29][30]. Findings from these studies demonstrate that perceived environmental health risks vary by SES, sex, race/ethnicity, and hazard experiences [25,27,31]. For instance, women compared to men and Blacks compared to Whites tend to perceive greater risk from environmental hazards such as pollution (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived risk is defined as an intuitive estimation of risk [21] or ''people's beliefs, attitudes, judgments and feelings, as well as, the wider social or cultural values and dispositions that people adopt, towards hazards and their benefits'' [22]. Risk perceptions associated with environmental hazards have largely explored technologies, reproductive health, and socioeconomic and racial differences in hazard exposures [21][22][23][24][25][26][27][28][29][30]. Findings from these studies demonstrate that perceived environmental health risks vary by SES, sex, race/ethnicity, and hazard experiences [25,27,31].…”
Section: Introductionmentioning
confidence: 99%